Inside Back Cover: Vanadium Hydroxide Cluster Ions in the Gas Phase: Bond‐Forming Reactions of Doubly‐Charged Negative Ions by SO2‐Promoted V−O Activation (Chem. Eur. J. 49/2017). Issue 49 (21st July 2017) - Troiani, Anna; Rosi, Marzio; Garzoli, Stefania; Salvitti, Chiara; de Petris, Giulia
Abstract : Doubly‐charged vanadium cluster anions undergo fast and efficient bond‐forming reactions, producing singly‐charged products. The charge separation process does not occur by exothermic electron transfer or fragmentation, but by reaction with sulfur dioxide, which promotes the breakage of strong V−O bonds and formation of new V−O and S−O bonds. More information can be found in the Communication by A. Troiani, G. de Petris et al. on page 11752 .